I can't keep my own secrets : six-word memoirs by teens famous + obscure : from Smith magazine - Fershleiser, Rachel.; Smith, Larry, 1968- (HarperTeen, 2009)
Collects memoirs from hundreds of teenagers composed of six words, ranging from the humorous to inspiring and dramatic, and includes six-word autobiographies from popular teenage celebrities.